PERFORMANCE OF SOME NEWLY DEVELOPED SUGARCANE GENOTYPES FOR SOME QUANTITATIVE AND QUALITATIVE TRAITS UNDER THATTA CONDITIONS - S. Junejo; G. M. Kaloi; R. N. Panhwar; M. Chohan; A. A. Junejo; A. F. Soomro (Journal of Animal and Plant Sciences, 2010)
Investigations were carried out at National Sugar Crops Research Institute (NSCRI), Thatta to assess the performance of different sugarcane genotypes under agro-climatic condition of Thatta during 2006-07. Twelve sugarcane genotypes developed from exotic fuzz (true seed) of USA origin along with one local check as standard variety Thatta-10 were evaluated for their cane yield, yield components and quality performance subsequently in 4th cycle. The behavior of the genotypes with regard to cane yield, yield components and quality remained variable during the study. The data indicated that the genotypes HoTh-610, HoTh-607 and check variety Thatta-10 remained superior by producing maximum average cane yield of 112.66, 106.66 and 106.00 t ha-1, respectively.While, the genotypes HoTh-640, HoTh-641 and HoTh-642 were ranked next to check variety on account of producing average cane yield of 103.0, 100.0 and 100.0 t ha-1, respectively. Moreover, the genotypes HoTh-614, HoTh-612, HoTh-633 and HoTh-618 occupied intermediate position by producing average cane yield of 94.0, 93.00, 89.66 and 82.0 t ha-1, respectively. While, in case of commercial cane sugar percentage, the data indicated that the genotypes HoTh-642 and HoTh-641were identified as high sugar containing on account of producing maximum CCS of 13.43% and 12.99%, respectively. Moreover, the genotypes HoTh-607, HoTh-606, HoTh-640, HoTh-610 and HoTh-618 also appeared to be the good sugar containing with CCS of 12.72, 12.42, 12.40, 12.36 and 12.35%, respectively, against Thatta-10 (11.56% CCS). All the genotypes along with Thatta-10 were also less susceptible to borer complex infestation.
Keywords: Cane yield; genotypes; sugar cane; yield components